The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/su10093161
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Measurement of the Firms’ Resources and Capabilities Applied to Eco-Innovation Projects from a Resource-Based View Perspective

Abstract: Interest from academics, policy–makers and practitioners in eco-innovation has increased as it enables the optimization of the use of natural resources improving competitiveness and it provides a conceptual framework for corporate sustainability. In this context, this paper provides an in-depth analysis and a wide classification of the specific indicators for the integrated measurement of eco-innovation projects in business from a resource-based view (RBV). The specific metrics were tested to measure the econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 154 publications
(318 reference statements)
2
70
0
5
Order By: Relevance
“…Complementing these studies, the present research suggests that buyers value added, as an external resource, moderates the effects of competitor orientation on EIC. Our results indicate that fostering buyers value added may help firms to enhance the relationship between competitor orientation and EIC [89,90]. As such, this article sheds new light on the role of buyers value added in affecting a firm's EIC.…”
Section: Managerial Implicationsmentioning
confidence: 64%
“…Complementing these studies, the present research suggests that buyers value added, as an external resource, moderates the effects of competitor orientation on EIC. Our results indicate that fostering buyers value added may help firms to enhance the relationship between competitor orientation and EIC [89,90]. As such, this article sheds new light on the role of buyers value added in affecting a firm's EIC.…”
Section: Managerial Implicationsmentioning
confidence: 64%
“…On the other hand, it facilitates the integration of principles and lean process management practices in the scope of a pro-eco-innovation orientation. For instance, Portillo-Tarragona et al [18] showed that companies implement eco-innovation solutions based on different certifications (e.g., ISO 14001 and ISO 50001 standards), which refer directly to the quality principle. Pacheco et al [19] emphasized that eco-innovation in a lean environment represents an opportunity for cost reduction, sustainable growth, and the enhancement of corporate image vis-à-vis customers.…”
Section: Discussionmentioning
confidence: 99%
“…A great number of firms deemed internal environmental orientation as a kind of pro-environmental culture and climate [14,29,30]. According to RBV, organizational culture and climate can be deemed as important resources helping firms gain sustainable competitive advantages [8,23,24]. Perceiving organizational culture and climate as resources can shape firms' strategic vision and motivate employees to care about the environment, which might be conductive to the implementation of green innovation [14].…”
Section: Environmental Orientation and Green Innovationmentioning
confidence: 99%
“…Resource-based view (RBV) is also applied by previous studies to investigate the antecedents of green innovation [23,24]. RBV can be used to complement stakeholder theory, because firms may perceive stakeholders' satisfaction as an important asset [8,25].…”
Section: Introductionmentioning
confidence: 99%